Effect of Friction Time on the Mechanical and Microstructural Properties of AA6061 Joints by Continuous Drive Friction Welding - Tashkandi, M. A.; Mohamed, M. I. (Engineering, Technology & Applied Science Research, 2020)
Friction welding is becoming a viable replacement of conventional joining methods. Continuous Drive Friction Welding (CDFW) is a type of friction welding used to join rods, tubes and similar shapes. Usually, the process contains a friction stage and a forging stage and the process parameters would be ticked accordingly. AA6061 is an Mg and Si aluminum alloy that is widely used in many industries. This research investigates the effect of friction time on the mechanical properties of AA6061 joints made with CDFW and the relation to the microstructure of the material and thermal profiles. It was found that AA6061 does not require a forging stage where solid joints are obtained without forging and did not fracture within the welding zones. Also, it was concluded that the process parameters are to be tailored in a way that produces a specific type of grain structure within the welding areas.